DELIVERY SYSTEM PADA RENCANA PEMBANGUNAN JALAN TOL JANGKA PANJANG - Dedy Gunawan; Citra Mira Dewi Boonastria (Jurnal HPJI (Himpunan Pengembangan Jalan Indonesia), 2022)
Abstract The high cost of logistics in Indonesia shows the low connectivity formed by the road network and by other modes of transportation. To improve connectivity, the Government is strengthening toll road infrastructure, with a target of reducing travel time on the island's main causeway to 1.9 hours per 100 km, and new toll roads being built and/or operating for 2500 km. Currently, about 27% of toll roads already built require Government support, both in the form of construction support and state capital participation, with the largest proportion on the island of Sumatera. In the long-term development plan, up to 2030, there are 36% of toll roads indicated to require Government support, the majority of which are located on the island of Sumatera. This study discusses the delivery system for the planned toll road construction until 2030. The results show that up to 2030, there are around 36% of toll roads that will be built requiring Government support. Keywords: toll road network; toll roads; connectivity; Government support; delivery system Abstrak Tingginya biaya logistik di Indonesia menunjukkan rendahnya konektivitas yang dibentuk oleh jaringan jalan maupun oleh moda transportasi lainnya. Untuk meningkatkan konektivitas, Pemerintah memperkuat infra-struktur jalan tol, dengan target mengurangi waktu tempuh di jalan lintas utama pulau menjadi 1,9 jam per 100 km, dan jalan tol baru yang terbangun dan/atau beroperasi sepanjang 2500 km. Saat ini, sekitar 27% ruas jalan tol yang dibangun, membutuhkan dukungan Pemerintah, baik berupa dukungan konstruksi maupun penyertaan modal negara, dengan proporsi terbesar berada di Pulau Sumatera. Dalam rencana pem-bangunan jangka panjang, sampai dengan tahun 2030, terdapat 36% ruas jalan tol yang terindikasi membutuhkan dukungan Pemerintah, yang mayoritas berada pada Pulau Sumatera. Pada studi ini dibahas delivery system pada rencana pembangunan jalan tol hingga tahun 2030. Studi ini menunjukkan bahwa sampai dengan tahun 2030, terdapat sekitar 36% ruas jalan tol yang akan dibangun membutuhkan dukungan pemerintah. Kata-kata kunci: jaringan jalan tol; ruas jalan tol; konektivitas; dukungan Pemerintah; delivery system